Sports and recreation where fitness fits in - Mohd Salleh Aman (University of Malaya Press, 2015)
Sports, recreation and fitness - where does it all fit in? With megabucks involvement in sports, and misconception that recreation is just for hobbies and pastime, this book strings in fitness as a common denominator in all. Tracking their development in communities through healthy lifestyle pursuits, associations, governmental, national and international levels for society integration and cohesion. For the curious, beginners or practising fitness enthusiasts, for the sportsmen and women alike and for aspiring parents who wants to sports/ recreation/fitness -'nised' their child, this book gives a background of things past and things to come. It defines the realm and scope of sports, recreation and fitness through the years.